Proyectos e iniciativas docentes relevantes en contexto de pandemia (Ariadna Ediciones, 2021)
In this fourth book, the results of some Projects sponsored by the Academic Vice President of the University of Santiago de Chile and that were developed by academics, academics, and teachers for hours of classes of the Faculty are reflected. Chapters worked on by academics, academics and professionals in the area of teaching from other Universities and Institutions are also published.